Making of Evalution’s Information System of Lecturer's Lecture and Major’s Service-Based Web in PTIK Major FKIP UNS - Rochmah, Irma Nuur; Yuana, Rosihan Ari; Maryono, Dwi (Universitas Sebelas Maret, 2017)
The quality of education of a study program can be measured from the level of customer satisfaction with the existing service. In accordance with ISO 9001: 2008, an organization should measure and obtain information related to customers and customers. Measurements and information that can be done survey data on customer satisfaction. From this survey data, Informatics and Computer Education Study Program can follow which aspect need improvement for program quality. One way to get survey data by doing the evaluation. In the Study Program of Informatics and Computer Engineering, evaluation using application form online form. The study program does not yet have its own evaluation information system. Therefore, the purpose of this research is to produce information technology and pelaynaan web-based program in the Study Program (Prodi) Educational Engineering and Computer Informatics and to determine the level of the feasibility of information. In this study used research and development model with the first phase of the preliminary study, the second stage of product development and the last stage. At the product development stage is done by using software development model. From the stages of inputs obtained from the assessment of students on lecturers' lectures and prodi services in Education Program Informatics and Computer Engineering. The result of evaluation of lecturers' lectures and prodi services by selected students with their rena as output that can be seen by lecturer and admin. A system that can be used to help the services that have been given to the students, both in lecturers' lectures and prodi services. The results of this study, first, has created information and web-based programming services in Informatics and Computer Engineering Education Program, FKIP, UNS. Second, the feasibility of information and product and service development, Informatics and Computer Engineering Education Study Program, FKIP, UNS conducted by expert system with percentage 89,34% and get very eligible category, from material expert gets 91,76% with category very eligible and from the students get the percentage of 83.32% with very decent category.Keywords: information system, lecturer lecture evaluation and prodi service, web